2003
DOI: 10.1159/000073967
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human Polymeric Immunoglobulin Receptor <i>(PIGR)</i> 3&prime;UTR and Differential Expression of <i>PIGR</i> mRNA during Colon Tumorigenesis

Abstract: The human cell lines VACO-235 and VACO-411 constitute a novel in vitro model of colon adenoma to carcinoma progression. By differential display RT-PCR we identified a transcript that is expressed in the parental nontumorigenic adenoma line (VACO-235E), but is not expressed in the tumorigenic daughter (VACO-235L) or granddaughter (VACO-411) lines. This cDNA represents a previously uncharacterized portion of the 3′UTR of human PIGR. Human PIGR mRNA was found to be highly expressed in normal colon epithelium, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Establishing the role of pIgR in EMT also helps to resolve the long-standing conflict on the clinical relevance of pIgR in tumor progression (23,24,5862). This is a reminiscent of the debate about the significance of EMT in tumor progression and its relevance in human cancers, which was not established until recently because EMT is transient and reversible (10,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Establishing the role of pIgR in EMT also helps to resolve the long-standing conflict on the clinical relevance of pIgR in tumor progression (23,24,5862). This is a reminiscent of the debate about the significance of EMT in tumor progression and its relevance in human cancers, which was not established until recently because EMT is transient and reversible (10,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported that expression of pIgR is down-regulated in sporadic colorectal tumors in humans. 1517 A common feature of these conditions is rapid proliferation of relatively undifferentiated epithelial cells, which may not respond properly to microbial and host factors that maintain pIgR expression under homeostatic conditions and enhance pIgR expression during infections.…”
Section: Down-regulation Of Pigr Expression In Inflammatory Bowel Dismentioning
confidence: 99%
“…In a small case series (n = 42) Gologan et al found PIGR-negative adenocarcinomas in the distal esophagus and GEJ to be associated with lymph node metastasis and a trend towards reduced survival [9]. Low PIGR expression has also been shown to correlate with progression from colon adenoma to carcinoma [10] and with poor prognosis in colon cancer [11]. Furthermore, loss of PIGR expression has been linked to tumour progression in non-small cell lung cancer [12] while overexpression of PIGR has been associated with the less aggressive type 1 endometrial cancer [13] as well as correlating with a better prognosis in bladder cancer [14] and epithelial ovarian cancer [15].…”
Section: Introductionmentioning
confidence: 99%